The evaluation of venture capital investments using real option approach - Posza, Alexandra (Marketing & Menedzsment, 2020)
THE AIMS OF THE PAPER This study attempts to explore the links between venture capital (VC) investments and the real option approach (ROA) with analyzing the characteristic features of the venture capital investments and their process. The real options can be examined as a way of thinking and evaluation method and the study’s aim is to show that real option approach can provide an answer to the valuation challenges of venture capital investments. METHODOLOGY The choice of the appropriate valuation method requires consideration of its conditions of application, which, in the case of real option theory, result from the examination of uncertainty, flexibility and irreversibility. The venture capital investments are characterized by a high degree of uncertainty and risk, which can also be traced back to the provision of financing to innovative, early-stage companies. Real option theory also provides venture capital investors with professional experience through their active role in decision-making. The study evaluates a Hungarian start-up company venture capital investment with the help of a traditional discounted cash flow method and two real option valuation models: Black – Scholes model and binomial pricing model. Then a sensitivity analysis is prepared to analyze the value driver effect on option value and a volatility analysis to verify the importance of high-degree of uncertainty in real option valuation. MOST IMPORTANT RESULTS The paper concludes that the option-based valuation methods are more suitable for evaluating venture capital investments than other approaches such as the discounted cash flow methods, and the embedded flexibility can be determined by the real option approach. The binomial pricing model points out the advantages of staging investments with the higher real (call) option value. Besides the real option valuation, the sensitivity analysis shows a positive effect of the present value of the underlying assets, the time to maturity, the risk-free interest rate and volatility on the call option value. The analysis of the volatility emphasizes the importance of the degree of uncertainty in real option valuation. RECOMMENDATIONS The real option approach ensures proper evaluation of venture capital investment, avoiding the undervaluation and taking advantage of staging and timing investments in practice. Acknowledgment: Supported by the ÚNKP-19-3 New National Excellence Program of the Ministry for Innovation and Technology.